2018
DOI: 10.1039/c8ce01183d
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional modifications induced by X-ray nanopatterning in Bi-2212 single crystals

Abstract: We have investigated the modifications induced in the high-Tc superconductor Bi2Sr2CaCu2O8+δ (Bi-2212) by X-ray nanopatterning, which is an innovative, photoresist-free, direct-writing approach recently used to fabricate proof-of-concept electrical devices [Truccato et al., Nano Lett. 2016, 16, 1669. By means of combined synchrotron microdiffraction and electrical transport measurements carried out on the same Bi-2212 microcrystal, we show that hard X-ray irradiation with fluences of the order of 10 12 J/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 43 publications
2
11
1
Order By: Relevance
“…Each d -spacing was obtained evaluating the centroid position on the curves resulting from the radial integration of a maximum projection of a 10–20° φ scan with a fine step. The value obtained for the crystal in this pristine condition is c = 30.536(5) Å, which corresponds to a heavily OD regime. , …”
Section: Data Treatments Results and Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Each d -spacing was obtained evaluating the centroid position on the curves resulting from the radial integration of a maximum projection of a 10–20° φ scan with a fine step. The value obtained for the crystal in this pristine condition is c = 30.536(5) Å, which corresponds to a heavily OD regime. , …”
Section: Data Treatments Results and Discussionmentioning
confidence: 77%
“…A rocking curve of reflection (006 1) was measured with an angular resolution of 0.01°at this position revealing a FWHM ≅ 0.06°, which indicates a very good crystallinity of this sample that is comparable to the free-standing Bi-2212 crystals analyzed by our group in a previous experiment. 29 In order to complete the characterization of the region prior to damaging, a y,z-scanning was acquired around the position D1 at the ϕ value coinciding with the maximum of the rocking curve. Figure 4a shows the maximum intensity projection of this measurement for the same portion of the detector as in Figure 3a.…”
Section: Data Treatments Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this background, we have recently demonstrated the feasibility of a new patterning concept, based on a resist-free method, which exploits the structural and electrical modifications induced in condensed matter by high-intensity nanometric beams from third-generation synchrotrons (Bonino et al, 2019;Pagliero et al, 2014;Truccato et al, 2016;Mino et al, 2017Mino et al, , 2019. For example, by irradiating the high-temperature superconductors Bi 2 Sr 2 CaCu 2 O 8+ and YBa 2 Ca 3 O 7À with a 17 keV nanobeam with a flux of $10 11 photons s À1 , a change in the electrical behaviour was related to an increase in the crystal mosaicity and a depletion of the doping oxygen content (Bonino et al, 2018(Bonino et al, , 2019. Following these findings, we exploited these local modifications to nanopattern three Bi 2 Sr 2 CaCu 2 O 8+ microcrystals, finally fabricating electrical devices based on the Josephson effect (Pagliero et al, 2014;Truccato et al, 2016;Mino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some of us have already shown that, using synchrotron radiation nanoprobes with sizes of the order of 50 Â 50 nm 2 and modifying the corresponding photon flux and dose, it is possible to switch from ordinary material characterization to material modification. [21][22][23][24][25][26][27] In the case that a superconducting oxide is irradiated in an approximately uniform way, this treatment corresponds to a variation of its oxygen doping level, [28][29][30] but if only some carefully designed portions are irradiated, a current path can be drawn in the material in such a way to fabricate a Josephson device. [31] Thus, the whole technique can be considered an alternative X-ray nanopatterning (XNP) method to locally introduce defects in oxides and fabricate devices as desired without etching the crystals.…”
mentioning
confidence: 99%